Implementation of Marine Pollution 73/78 Annex V on the Meratus Benoa Ship to Prevent Marine Pollution - Dion Adi Deny; Muhamad Imam Firdaus; Bugi Nugraha; Tri Haryanto (International Journal of Science and Environment (IJSE), 2026)
Indonesia ranks second globally in ship-generated marine debris pollution, driven by 32,587 vessels producing unmanaged plastic and food waste that harms ecosystems and human health. This study analyzes MARPOL 73/78 Annex V implementation on MV. Meratus Benoa to identify constraints and recommend improvements. Employing a qualitative case study approach during 12-month sea practice (July 2024–July 2025), the population comprised 20 crew members, with purposive sampling of Chief Officer and Boatswain as key informants. Instruments included observation guidelines, semi-structured interviews, and documents such as Garbage Management Plan; data analysis followed interactive iterative reduction, display, and verification models. Findings reveal principled compliance through waste segregation, Garbage Record Book logging, and supervision, yet suboptimal due to absent incinerator, limited storage, short port stays, and inconsistent crew discipline despite safety meetings enhancing adherence. Conclusions recommend onboard facility upgrades, routine training, and port coordination to achieve 70% plastic pollution reduction targets, informing national maritime sustainability.